Study of the influence of the environment on the efficiency of induction heating of low-temperature heat pipe - Vashchyshak, Iryna; Vashchyshak, Serhii; Mazur, Tetiana; Mazur, Myroslav (Physics and Chemistry of Solid State, 2024)
The influence of ferromagnetic materials of three cylindrical structural steel cores and a spiral weave magnetic stainless-steel core on the efficiency of induction heating of the coolant in a low-temperature oppression heat pipe is investigated. Two cores were intended for use under the oppression layer, and two - behind the oppression layer made of stainless mesh without magnetic properties. The efficiency of induction heating using a cylindrical coil wound on the surface of the tube was studied. An experimental setup was assembled from a heat pipe, a cylindrical induction coil put on its lower part, a pulse generator, an amplifier, a power switch, a wattmeter, two thermocouples and a timer. Experiments have shown that at a low frequency of heat pipes with a vertical orientation, with a decrease in the wall thickness of the iron cylindrical core and an increase in its radius, the efficiency of induction heating increases. For heat pipes with arbitrary orientation in space, the highest efficiency of induction heating is provided by a cylindrical thin-walled single-layer core placed after the oppression layer. But the highest operational reliability and high efficiency of induction heating can be provided by a solid cylindrical core, or a spiral-weave core made of magnetic stainless steel AISI 430 or 439, wound on a heat-resistant plastic frame with holes for the coolant movement. The maximum radius and minimum mass of the core should provide the highest intensity of heating of the coolant per unit of time.